Analisis Pengaruh Kualitas Pelayanan Terhadap Kepuasan Nasabah PT.BPR Syariah Dana Mulia Surakarta - Pardanawati, Sri Laksmi; , Drs. Wiyadi, M.M., Ph.D; , Dr. Anton Agus Setyawan, M.Si (2014)
This research aims; to analyze the influence of service quality consisting of Compliance dimension, Assurance, Reliability, Tangible, Emphaty, Responsiveness, towards Customers' satisfaction. The research type that is used is survey research. It is a kind of research which takes samples from population by using questionaires as a means to collect primary data. Data analysis is done by multiple linear regression, the result of analysis shows the service quality CARTER model consisting of Compliance, Assurance, Reliabilty, Emphaty, Responsiveness with (F test ) and partially (t test) influences positively and significantly towards customers of PT. BPR Syariah Dana Mulia Surakarta. Dimension of service quality that is the most dominant towards customers' satisfaction is Assurance.